Ocular morbidity and its relation to classroom lighting among middle-school students of government high schools in Goa - Cacodcar, Jagadish A.; Bicholkar, Abhishek; Wagle, Nikita; Oliveira, Annet (International Journal Of Community Medicine And Public Health, 2017)
Background: School children form an important target group for a Nation and any ocular morbidity in this age group has huge physical, psychological and socio-economical implications. Research studies have shown that illumination has a significant effect not only on scholastic performance of the students, but also on their physical and mental health. The current study was carried out to assess the prevalence of ocular morbidities among students of high schools of Sanquelim Taluka in Goa, and to assess possible association between ocular morbidity and level of classroom and blackboard illumination. Methods: Students of class 6, 7 and 8 of eight randomly selected schools were interviewed using a semi-structured questionnaire for personal details and visual symptoms. Visual acuity testing was done using Snellen’s chart. Classroom and blackboard illumination were assessed separately using standard calibrated digital Lux meter (LX-10101B). Results: Using Snellen’s chart, 83 (18%) of the study subjects were found to have visual morbidity. The measurement of illumination levels showed that out of the 24 classrooms and blackboards evaluated, 15 (62.5%) classrooms and 9 (37.5%) blackboards had inadequate illumination. Classroom illumination was found to have significant association (p=0.04) with visual morbidity. Conclusions: A significant number of classrooms (62.5%) and blackboards (37.5%) had below recommended illumination levels. Regular evaluation of infrastructure should be done to ensure adequate artificial illumination of the classrooms.